How do you write a quadratic function in standard form whose graph passes through points (2,-4), (3,-7), (1,-3)?
2 Answers
Explanation:
Here's one method...
Putting the points in increasing order of
#(1, -3)# ,#(2, -4)# ,#(3, -7)#
Note that the
Hence we can analyse this as a sequence of
Write down the sequence of
#color(blue)(-3), -4, -7#
Write down the sequence of differences between pairs of consecutive terms:
#color(blue)(-1), -3#
Write down the sequence of differences of differences:
#color(blue)(-2)#
Having reached a constant sequence (albeit of just one term), we can write a general formula for a term of the initial sequence of
#a_n = color(blue)(-3)/(0!)+color(blue)(-1)/(1!)(n-1)+color(blue)(-2)/(2!)(n-1)(n-2)#
#color(white)(a_n) = -3-n+1-n^2+3n-2#
#color(white)(a_n) = -n^2+2n-4" "# for#n = 1,2,3#
Hence our function can be written:
#f(x) = -x^2+2x-4#
Explanation:
Here's a general purpose method for matching a polynomial to a set of points...
The formula
Given a set of points:
#{ (x_1, y_1),...,(x_n, y_n) }#
with distinct values
A polynomial that passes through them is:
#((x-x_2)(x-x_3)...(x-x_n))/((x_1-x_2)(x_1-x_3)...(x_1-x_n))y_1 +#
#((x-x_1)(x-x_3)...(x-x_n))/((x_2-x_1)(x_2-x_3)...(x_2-x_n))y_2 + ...#
#+ ((x-x_1)(x-x_2)...(x-x_(n-1)))/((x_n-x_1)(x_n-x_2)...(x_n-x_(n-1)))y_n#
#= sum_(k=1)^n (prod_(j = 1, j != k)^n (x-x_j)/(x_k-x_j)) y_k#
How does it work?
That may look rather complicated, but notice how it works:
Looking at the first expression:
#((x-x_2)(x-x_3)...(x-x_n))/((x_1-x_2)(x_1-x_3)...(x_1-x_n)) = prod_(j = 2)^n (x-x_j)/(x_1-x_j)#
Note that:
-
It takes the value
#1# when#x=x_1# since the numerator and denominator become identical. -
It takes the value
#0# when#x=x_k# for any#k# apart from#1# , since one of the factors in the numerator will be#0# . -
It is a polynomial of degree
#n-1# .
So when we multiply this by
Summing this with the similar polynomials for
Application
In the given example, with points:
#{ ((x_1, y_1) = (2, -4)), ((x_2, y_2) = (3, -7)), ((x_3, y_3) = (1, -3)) :}#
We can write:
#f(x) = ((x-3)(x-1))/((2-3)(2-1))(-4)+((x-2)(x-1))/((3-2)(3-1))(-7)+((x-2)(x-3))/((1-2)(1-3))(-3)#
#color(white)(f(x)) = 4(x^2-4x+3)-7/2(x^2-3x+2)-3/2(x^2-5x+6)#
#color(white)(f(x)) = -x^2+2x-4#